Senior High School Students’ Perceptions on Using Songs as English Learning Media - Pratiwi, Shindy Septiyani; Sulaksana, Johan; Ramadhan, Noval Ilham; Darsih, Endang (UM Purwokerto Press, 2025)
This study explores senior high school students’ perceptions of using songs as a medium in english language learning. Recognizing the potential of songs to enhance motivation, engagement, and language proficiency, the research focuses on four 12th-grade students majoring in Computer and Network Engineering at SMKN 2 Kuningan. Utilizing a descriptive quantitative approach, data were collected through questionnaires comprising closed and openended questions. Findings reveal that students hold positive perceptions of using songs in learning English, noting benefits such as improved pronunciation, better vocabulary retention, increased motivation, and enhanced listening skills. The pop genre was most favored due to its clear and simple lyrics. Despite the overall enthusiasm, students identified some challenges, including difficulty understanding lyrics without written text and unclear pronunciation. Nonetheless, all participants recommended more frequent integration of songs into English instruction, emphasizing the engaging and enjoyable nature of this approach. These results suggest that incorporating music into language education can significantly contribute to student learning outcomes, especially in vocabulary acquisition and listening comprehension.